Sensing Bioavailable Water Content of Granulated Matrices: A Combined Experimental and Computational Study - Ria Ghosh; Neha Bhattacharyya; Amrita Banerjee; Lopamudra Roy; Debdatta Mukherjee; Soumendra Singh; Arpita Chattopadhyay; Tapan Adhikari; Samir Kumar Pal (Biosensors, 2023)
This paper represents the synthesis, characterization and validation of a cobalt chloride functionalised nano-porous cellulose membrane, a unique sensor for non-contact measurement of water potential in various biomedical and environmentally important matrices. The developed nano sensor, along with associated electronic components, is assembled as a prototype device called “MEGH” (Measuring Essential Good Hydration) to measure essential hydration of matrices of both environmental and biomedical importance, including soil and human skin. The relative humidity above the soil surface in equilibrium with the soil moisture has been studied for both hydrophobic and hydrophilic soil types. Our studies confirm that the percentage of water available to plants is greater in hydrophobic soil rather than in hydrophilic soil, which has also been corroborated using simulation studies. Furthermore, the requirement of hydration in human skin has also been evaluated by measuring the water potential of both dry and moist skin.